From Aegean, over Euphrates, to Indus: the life and the work of Harald Hauptmann - Bobokhyan, Arsen (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
Harald Hauptmann (19 April, 1936 – 2 August, 2018), one of the most prominent representatives of world’s archaeological community, passed away at the age of 82. As representative of classical German archaeological school, H. Hauptmann has been very influential in shaping what Colin Renfrew calls ‘Great tradition’ of archaeology characterised by rigorous excavations carried out on a grand-scale, systematic inventory and careful categorization of artifacts, thorough and comprehensive publication of finds: this is a true archaeology carried out as a scientific experiment. In a dissertation concerning the history of the Keban Dam Rescue Project, in which H. Hauptmann played his great role, Laurent Dissard correctly writes (p. 24): ‘At Keban, H. Hauptmann who excavated at Norşuntepe can be placed alongside Winckelmann, Dörpfeld, Bittel and Blegen as some of the “great men” of German archaeology’. H. Hauptmann realised his scientific experiments in the time period between the Neolithic and the Iron Age and in a space stretching from South-Eastern Europe, particularly from Greece (during the first stage of his archaeological career), to the Near East, particularly to Asia Minor and Caucasia (during the second stage) and beyond to South Asia, particularly to mountainous regions of Karakorum (during the last stage).